MOLECULAR SYSTEMATICS AND DIVERGENCE ESTIMATES OF PAKISTANI MOSQUITOES IN GENUS ANOPHELES - N. Ali; F. Zaidi (Journal of Animal and Plant Sciences, 2014)
The present study explored the phylogenetic utility of mt-ND5 gene sequences for mosquitoes in genus Anopheles. Phylogenetic tree employing the Maximum Parsimony methods in PAUP strongly supported the traditional taxonomy of genus. Subgenus Anopheles represented by a single species i.e. Anopheles nigerrimus initially separated out from the rest with a strong bootstrap value of 100. Subgenus Cellia representing bulk of Pakistani mosquitoes showed a monophyletic lineage (bootstrap value: 97). Using two fossil calibration points (both at 34 Mya) mtDNA divergence times were estimated within a sympatric group of Anophelines of Pakistan. The divergence time between Subgenera Anopheles and Cellia was estimated at approximately 6 million years ago i.e. between mid to late Pliocene. Series Neocellia (Anopheles splendidus, Anopheles stephensi, Anopheles annularis, Anopheles pulcherrimus) diverged some 5.7 million years ago from Myzomyia (Anopheles culicifacies and Anopheles fluviatilis), while speciation within the respective series took place during the Pleistocene about 0.7 million years ago. The present study, shows Pliocene as the starting point for mosquito evolution while Pleistocene as the point of diversification. The ongoing climate change, uplifting of Himalaya, evolution of a monsoon system, rising and falling of the sea level are perhaps those features of Pleistocene that might have led to the process of speciation in genus Anopheles of Pakistan.The present study explored the phylogenetic utility of mt-ND5 gene sequences for mosquitoes in genus Anopheles. Phylogenetic tree employing the Maximum Parsimony methods in PAUP strongly supported the traditional taxonomy of genus. Subgenus Anopheles represented by a single species i.e. Anopheles nigerrimus initially separated out from the rest with a strong bootstrap value of 100. Subgenus Cellia representing bulk of Pakistani mosquitoes showed a monophyletic lineage (bootstrap value: 97). Using two fossil calibration points (both at 34 Mya) mtDNA divergence times were estimated within a sympatric group of Anophelines of Pakistan. The divergence time between Subgenera Anopheles and Cellia was estimated at approximately 6 million years ago i.e. between mid to late Pliocene. Series Neocellia (Anopheles splendidus, Anopheles stephensi, Anopheles annularis, Anopheles pulcherrimus) diverged some 5.7 million years ago from Myzomyia (Anopheles culicifacies and Anopheles fluviatilis), while speciation within the respective series took place during the Pleistocene about 0.7 million years ago. The present study, shows Pliocene as the starting point for mosquito evolution while Pleistocene as the point of diversification. The ongoing climate change, uplifting of Himalaya, evolution of a monsoon system, rising and falling of the sea level are perhaps those features of Pleistocene that might have led to the process of speciation in genus Anopheles of Pakistan.
Keywords: malaria; Pakistan; Anopheles; Pleistocene